To democratize and strengthen forest utilization in Peru - Dourojeanni, Marc (2022)
Exceptions aside, the production of timber from natural forests in Peru does not result from the application of sustainable forest management. Therefore, wood exploitation degrades the forest and contributes to severely reduce its ecosystem services. The most evident direct cause of degradation has been the transfer of responsibility for forest management to the private sector, which, under the current and predicable economic and social context, is unable to carry out a sustainable management that is also profitable (Dourojeanni 2019, 2020). In the context of a new national forest policy that prioritizes the maintenance of environmental services (Dourojeanni et al 2021, CNF 2022) it is being proposed to gradually transfer this responsibility to the State and local communities, without undermining the private role in the extraction, transformation, and commercialization phases. Forest management would be carried out through local management units with full participation of local actors and administrative and financial autonomy, based on the public auction of standing trees. This note describes the proposal, discusses its justification, its advantages, and eventual disadvantages, and proposes a practical alternative for its implementation.